2007
DOI: 10.1007/s10750-007-9177-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of a monotypic and diverse native aquatic plant bed on a macroinvertebrate assemblage; an experimental implication of exotic plant induced habitat

Abstract: Aquatic plants mediate ecological processes in aquatic habitats, specifically predator-prey (bluegill sunfish (Lepomis macrochirus Rafinesque)-macroinvertebrate) interactions. Macroinvertebrate colonization is directly and indirectly influenced by substrate heterogeneity, interstitial space, and surface complexity. Exotic invasive plant species, such as Hydrilla verticillata L.F. Royle, may alter the available structure in aquatic habitat by creating a shift to a homogeneous habitat, thus affecting the macroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…Greater macroinvertebrate diversity, richness and abundance might be expected at the vegetated site, given the presence of emergent plants which should have increased habitat heterogeneity, thus providing a greater variety of shelter and food resources (Spänhoff & Arle 2007, Theel et al 2008. In Lower Peirce, the weed-cutting regime reduced the inlake vegetation, leaving a relatively uniform silt/sand benthos with occasional woody debris.…”
Section: Discussionmentioning
confidence: 99%
“…Greater macroinvertebrate diversity, richness and abundance might be expected at the vegetated site, given the presence of emergent plants which should have increased habitat heterogeneity, thus providing a greater variety of shelter and food resources (Spänhoff & Arle 2007, Theel et al 2008. In Lower Peirce, the weed-cutting regime reduced the inlake vegetation, leaving a relatively uniform silt/sand benthos with occasional woody debris.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrilla verticillata (L. f.) Royle, Hydrocharitaceae) (Theel et al, 2008) the invasion of white ginger lily shifted aquatic insect assemblage composition probably due to habitat alterations. Our results showed that white ginger lily shifted aquatic insect assemblages when compared with other native vegetation bank profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Pelagic-and epiphytic algae exhibited different seasonal distribution patterns, suggesting that they showed opposing relationship with the seasonal gradient of macrophyte cover. In general, epiphytic algae were strongly influenced on the seasonal development of macrophyte species due to qualitative and quantitative change of substrate surface of stem or root in accordance with season (Castro et al 2007, Theel et al 2008. The colonization by various macrophytes species increases the substrate surface for attachment of epiphytic algae, thus the macrophytes' dominance can support high abundance of epiphytic algae.…”
Section: Discussionmentioning
confidence: 99%